Compulsory Rotating Internship Regulations Draft, 2021: A long-needed boost for medico-legal training - Chandra Bhargava, Daideepya; Jadav, Devendra; Tak, Manish (Journal of Indian Academy of Forensic Medicine, 2021)
The internship is a phase of training wherein a medical graduate  will acquire the skills and competencies for medical and health  care practice under supervision in preparation for independent,  unsupervised primary care. The learning methods and modalities  have to be initiated and inculcated during the M.B.B.S. course,  with a larger number of hands-on sessions preceding actual  clinical training. Currently doctors after graduation either join  government service or go for private practice, or proceed for  postgraduation/further studies. These medical graduates are  mostly not exposed to any training on medicolegal issues during  their internship which can have serious consequences in their  1,2 practice of medicine.
Keywords: Compulsory; medico-legal training